2021
DOI: 10.1002/ajh.26308
|View full text |Cite
|
Sign up to set email alerts
|

Multiple inducers of endothelial NOS (eNOS) dysfunction in sickle cell disease

Abstract: A characteristic aspect of the robust, systemic inflammatory state in sickle cell disease is dysfunction of endothelial nitric oxide synthase (eNOS). We identify 10 aberrant endothelial cell inputs, present in the specific sickle context, that are known to have the ability to cause eNOS dysfunction. These are: endothelial arginase depletion, asymmetric dimethylarginine, complement activation, endothelial glycocalyx degradation, free fatty acids, inflammatory mediators, microparticles, oxidized low density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 127 publications
(213 reference statements)
0
5
0
Order By: Relevance
“…An important disease mechanism involves the release of hemoglobin into the circulation during intravascular haemolysis ( 14 ). The release of hemoglobin into the plasma during haemolysis potently inhibits endothelial nitric oxide signaling, leading to endothelial cell dysfunction and nitric oxide resistance ( 16 ). Studies have shown correlations between the rate of haemolysis and levels of platelet activation and procoagulant factors in the blood ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…An important disease mechanism involves the release of hemoglobin into the circulation during intravascular haemolysis ( 14 ). The release of hemoglobin into the plasma during haemolysis potently inhibits endothelial nitric oxide signaling, leading to endothelial cell dysfunction and nitric oxide resistance ( 16 ). Studies have shown correlations between the rate of haemolysis and levels of platelet activation and procoagulant factors in the blood ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcome is that the heterozygous mice; even in the absence of patent hematological differences compared to the controls; carry characteristic lesions of the tunica intima of small vessels, that are especially found in the liver, spleen, kidneys, and lungs. While anomalies of the endothelial lining associated with SCD-affected patients and mouse models have been previously reported [ 32 , 33 , 34 ], the evidence of their association with the SCT carrier condition is still fragmentary [ 35 , 36 ]. The histopathological differences among the SCD-affected, the SCT carrier, and control mice have been addressed in very few studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rs2070744 was found in the promoter region and rs1799983 within exon 7 (894 G>T, Glu-298Asp) and the frequency of these polymorphisms was particularly high in patients with severe SCD, associated with lower levels of plasma NO [199]. NO inducers should be considered as therapeutic tools in SCD [200,201]. Interestingly, evidence for the in vivo conversion of hydroxyurea to nitric oxide has been provided [202].…”
Section: Inducers Of Nitric Oxide In Scdmentioning
confidence: 99%